2011
DOI: 10.1097/gme.0b013e3182135442
|View full text |Cite
|
Sign up to set email alerts
|

Combined resistance and endurance exercise training improves arterial stiffness, blood pressure, and muscle strength in postmenopausal women

Abstract: Our findings indicate that a 12-week moderate-intensity combined circuit RE and EE training improves arterial stiffness, hemodynamics, and muscle strength in previously sedentary postmenopausal women. This study provides evidence that combined training may have important health implications for the prevention of hypertension and frailty in postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
93
4
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(111 citation statements)
references
References 35 publications
12
93
4
2
Order By: Relevance
“…Therefore, prescribing aerobic and resistance training in combination is proposed as an efficacious strategy to improve cardiovascular as well as musculoskeletal functions in the elderly. Previous study showed that moderate-intensity combined training improved arterial stiffness and greater muscle strength in postmenopausal women [24]. The present study, despite higher intensity combined training, results in decreased arterial stiffness by performing aerobic exercise after resistance training.…”
Section: Discussioncontrasting
confidence: 33%
See 1 more Smart Citation
“…Therefore, prescribing aerobic and resistance training in combination is proposed as an efficacious strategy to improve cardiovascular as well as musculoskeletal functions in the elderly. Previous study showed that moderate-intensity combined training improved arterial stiffness and greater muscle strength in postmenopausal women [24]. The present study, despite higher intensity combined training, results in decreased arterial stiffness by performing aerobic exercise after resistance training.…”
Section: Discussioncontrasting
confidence: 33%
“…Karavirta et al [23] reported that combined training increased muscle strength in 40-67-year-old men. Regarding vascular function, Figueroa et al [24] reported that a 12-week moderate-intensity combined training improved arterial stiffness, hemodynamics in postmenopausal women. Katie et al [25] showed that combined training reduced systolic blood pressure and improved vascular properties.…”
mentioning
confidence: 99%
“…Moreover, the discontinuation of the concurrent training program increased these patients' cardiovascular risk (Berent et al 2011). In postmenopausal women, combined strength and endurance training performed 3 days per week improved arterial stiffness and blood pressure (Figueroa et al 2011). These results are quite relevant given that, in addition to declines in muscle strength, menopause is associated with increased arterial stiffness.…”
Section: The Role Of Concurrent Training In Disease Treatmentmentioning
confidence: 58%
“…These reductions in MAP and AIx suggest an improvement in the functionality of the resistance arteries and therefore a reduction in CV risk. The results were novel (in the context specifically of green-exercise) but expected, as aerobic exercise programmes have previously been associated with improvements in CV risk and vascular haemodynamics, including MAP and AIx [53][54][55]. However, to the best of our knowledge, while Pretty et al [21] have demonstrated the beneficial impact of acute bouts of aerobic exercise whilst viewing scenes of nature on MAP, the effect of an 8-week green-exercise programme on MAP and AIx had not before been investigated.…”
Section: Discussionmentioning
confidence: 98%